The equidistant heptatonic scale of the Asena in Malawi - Van Zanten, Wim (International Library of African Music, 1980)
The musical scale of the Sena people of Southern Malawi can be characterised as an equidistant heptatonic tone system. Kubik (1968) reports: The equi-heptatonic tuning with its standard interval of 171 cents gives an unmistakable sound to the Asena bangwe. The same scale is used for the tuning of the large ulimba xylophones. The bangwe (a board zither) and the ulimba, belong, next to drums and rattles, to the most common instruments of the Asena in the Lower Shire Valley of Malawi.
Keywords: Sena (African people); African Music; Malawi